Managerial ownership, entrenchment and innovation - Mila Beyer; Dirk Czarnitzki; Kornelius Kraft (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
Principle-agent theory suggests managers might under-invest into R&D for reasons of risk tied to project failure, such as reduced remuneration and job loss. However, managers might over-invest into innovation for reasons of growth implying higher remuneration, power and prestige. Using a sample of 1,406 Belgian firms, we find, first, that managers holding no company shares under-invest into R&D compared to owners giving rise to the risk argument. Second, we find an inverse u-shaped relationship between the degree of managerial ownership and R&D. Thus, managers become entrenched, i.e. powerful enough to pursue their own interests. When entrenched, managers do not fear detrimental effects of risky innovation projects on their career, and hence tend to over-invest into innovation.
Keywords: G32; O31; O32; 330; corporate governance; managerial ownership; entrenchment; innovation; R&D investments